WAIST CIRCUMFERENCE DIFFERENCE OF SOMATOTYPE ELDERLY ON SAWUNGGALING SURABAYA - Yuni Kurniawaty (UPT Penerbitan Universitas Jember, 2017)
Background: Central obesity of elderly has been a health problem. Central obesity is related to a high risk of cardiovascular disease and metabolic disorders. While somatotype with endomorph type is significantly correlated to the waist circumference where waist circumference is one kind of central obesity measurement. The aim of this research is to determine whether there is a waist circumference difference among somatotype groups of elderly. Methods: The design of this research is cross sectional. The research population was elderly in RW 5 Sawunggaling Surabaya. The number of the sample was 80 respondents with simple random sampling technique. Waist circumference and 10 anthropometric measurements were done to the respondents. Somatotype calculation used Heath-Carter method. Basic characteristic data of the research subject used univariate analysis. Hypothetic test used Kruskal-Wallis test continued with Mann Whitney U test. Dependent variable of this research is waist circumference value. Independent variable in this research is somatotype elderly. Results: Kruskal-Wallis statistic test is p=0.003 where p<α (0.05) means there is a significant waist circumference difference among somatotype. Mann Whitney U test result shows a waist circumference difference in central somatotype group with endomorph p=0.019, central with endomorph-mesomorph p=0.006, central with mesomorph p=0.049, endomorph-mesomorph with mesomorph-ectomorph p=0.017, endomorph-mesomorph with ectomorph p=0.041, mesomorph with mesomorph-ectomorph p=0.023. Conclusion: Somatotype endomorph, mesomorph and endomorph-mesomorph waist circumference tend to be higher than another type because there is more body fat as a result of visceral digestion domination in endomorph type. Keywords: waist circumference, somatotype, elderly.